Requirements engineering of Malaysian radiological medical emergency response simulator. Issue 3 (3rd July 2018) - Ab. Hamid, Amy Hamijah binti; Rozan, Mohd Zaidi Abd; Ibrahim, Roliana; Deris, Safaai; Selamat, Ali; Yunus, Muhd. Noor Muhd.
ABSTRACT: The development of the Malaysian radiological medical emergency response simulator emphasized human factors according to the stakeholder's tacit and explicit knowledge. These human factors criteria were usability tested and analysed according to the socio-technical components. These analyses and interpretations were corroborated by the statistical criteria which emphasized on business process-based requirements modelling and simulation system development tools. Recent findings suggested that there were no differences of risk perceptions among these multi-agency stakeholders in the respective emergency planning framework and simulator. However, the stakeholders had differences in knowledge and experiences in the radiological and nuclear emergency planning framework (RANEPF). This paper analyses the proposed conceptual framework for further enhancement of the current RANEPF simulator. This development was in concurrence with the proposed hypothesis of the process factors and response diagram. The majority (75%) of the stakeholders and experts, who had been interviewed, witnessed and accepted that the simulator would be effective to resolve various types of disaster and resource management issues. We suggest further investigation to establish the additional functionality of the simulator as a strategist, condensed, concise, comprehensive public disaster preparedness and intervention guidelines to be a useful and efficient computer simulation.